Modelling the South African Inter-Bank Interest Rate Market using a Log-Normal Rational Pricing Kernel Model - Hammond, Graeme (African Institute of Financial Markets and Risk Management, 2020)
This dissertation examines the performance of two log-normal rational pricing kernel models and their calibration to the South African Inter-bank interest rate market. We investigate using Monte-Carlo simulation to price caps, floors and swaptions. Model-performance for both models was tested on single-strikes and entire volatility surfaces. Our results show that a one-factor model cannot reproduce the volatility smile present in the caps/floor market but can reproduce the at-the money swaption volatility surface. The two-factor model produces a better calibration to the volatility smile and captures most of the characteristics of the volatility surface.